Obesity and Breast Cancer: Molecular Interconnections and Potential Clinical Applications. (10th February 2016) - Simone, Valeria; D'Avenia, Morena; Argentiero, Antonella; Felici, Claudia; Rizzo, Francesca Maria; De Pergola, Giovanni; Silvestris, Franco
Abstract: Obesity is an important risk factor for breast cancer (BC) in postmenopausal women; interlinked molecular mechanisms might be involved in the pathogenesis. Increased levels of estrogens due to aromatization of the adipose tissue, inflammatory cytokines such as tumor necrosis factor- α, interleukin-6, and prostaglandin E2, insulin resistance and hyperactivation of insulin-like growth factors pathways, adipokines, and oxidative stress are all abnormally regulated in obese women and contribute to cancerogenesis. These molecular factors interfere with intracellular signaling in the mitogen-activated protein kinase and phosphatydilinositol-3-phosphate/mammalian target of rapamycin (mTOR) pathways, which regulate the progression of the cell cycle, apoptosis, and protein synthesis. In this context, structural defects of typical genes related to both BC and obesity, such as leptin, leptin receptor, serum paraoxonase/arylesterase 1, the fat mass and obesity-associated gene and melanocortin receptor 4, have been associated with a high or low risk of BC development. The early detection of these gene alterations might be useful as risk predictors in obese women, and targeting these pathways involved in the BC pathogenesis in obese women is a potential therapeutic tool. In particular, mTOR pathway deregulation concurs in both obesity and BC, and inhibition of this might disrupt the molecular interlinks in a similar manner to that of metformin, which exerts definite anticancer activity and is currently used as an antidiabetic drug with a weight-reducing property. The identification of both genetic and pharmacological implications on the prevention and management of BC is the ultimate aim of these studies. Abstract : Obesity is an important risk factor for breast cancer (BC) in postmenopausal women; interlinked molecular mechanisms might be involved in the pathogenesis. The structural defects of typical genes related to both BC and obesity have been associated with a high or low risk of BC development. The identification of both genetic and pharmacological implications on the prevention and management of BC is the ultimate aim of these studies.